Improved Reading and Writing Skills through the Random Method of Words on the Lesson Language in Elementary School - Totok Bintoro; Mardhatillah Mardhatillah; Riana Bagaskorowati; Murni Winarsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Research with the Title "Improving Reading and Writing Skills through Random Word Methods in Language Learning in Elementary Schools".  The main and fundamental problem in this study is the low reading and writing skills in the Language lessons of elementary school students, especially in the material that complements the story.  The problem that often arises in the learning process is that students using standard language still often have difficulty communicating with teachers. A very apparent problem faced is when constructing sentences to be said. The low reading and writing skills of students are caused because this arises because of the background of students who still use regional languages as their daily language. This research aims to improve reading and writing skills in various student skills improvement in Language lessons in elementary schools. This research is Classroom Action Research. The subjects and locations   of the study were 18 students with a composition of 10 male students and 8 female students. The instrument for collecting research data is to provide tests at the end of each cycle, and observation during the teaching and learning process. The results of the assessment show that the use of the Random Word method is very effective and fun in improving skills, reading, and writing. In pre-action 100% of students' reading and writing skills have not been completed. The effectiveness of the use of the method can be seen from the first cycle of reading skills of students (83%) still in the category of less, cycle II increases (72%) of students are in the category of excellent. Writing skills in the first cycle (16.16%) students were already skilled, (83.34%) students were not skilled. Meanwhile, in the second cycle of writing skills (100%) students are already skilled with an average score of 89. Some positive changes that occur in students. Especially on the change in reading skills, and writing students in following Language learning.